Μέτρηση της συγκέντρωσης αέριων και σωματιδιακών ρύπων σε πολυσύχναστους δρόμους της Πάφου - Ομήρου, Όμηρος (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος,Τεχνολογικό πανεπιστήμιο Κύπρου, 2013)
The present Master Thesis is being conducted, for the «Master of Science in Energy Resource Management», at the Environmental Science and Technology Department of the Cyprus University of Technology, under the supervision of Dr. Costa N. Costa, Associate Professor at the Department. From the late of the 20th century, facts show that the problem of air pollution is global, extending beyond national borders. The transport sector contribution to air pollution is about 30%. In many European cities, the air pollution problems are a result of the heavy vehicle traffic. Responsible authority in Cyprus for air quality is the Department of Labour Inspection. The aim of this study is to measure the concentration of gaseous and particulate pollutants on busy streets in Paphos. Data collection involved measurements of the gaseous pollutants: CO, SO2, NO2, NO O3, benzene, toluene, ethylbenzene, xylene and particulate pollutants PM-1, PM-2.5, PM-7, PM-10, TSP. Measurements were performed during the lasts summer, at 6 specific points of streets in Paphos. After the collection and analysis of measurements, data were compared with the limit values of the European Union. Results from the comparison between the measured and limit values, show the exceedances at each point. The results show exceedances in ozone levels, caused but the climate conditions in Cyprus, as well as slight excesses of particulate matter (PM-10 and TSP).
Keywords: Gaseous; Particulate; Air pollution